The Relationship Between Learning Outcomes of Basic Elements of Patterns and Elements of Preparation for Fashion Making - Riski Purwiningsih; Musdalifah Musdalifah (Jurnal Penelitian Pendidikan, 2026)
This study aims to determine the relationship between the learning outcomes of the Basic Elements of Patterns in phase E and the learning outcomes of the Preparation Elements of Fashion Making in phase F in the implementation of the Independent Curriculum at Vocational Schools of Fashion Expertise program. This study uses a quantitative approach with the type of ex post facto correlational research, because the variable data studied has occurred before the research was carried out. The population in this study consists of all students in grade XI of Fashion Dress at SMK YATPI Godong for the 2025/2026 Academic Year which totals 49 students and uses a total sampling technique where the entire population is used as a research sample. The research data was obtained through documentation of student learning outcomes in both learning elements. Data analysis began with a statistical descriptive test to describe the characteristics of the data, then continued with a normality test, and a Spearman Rank correlation test with the help of SPSS Statistics 26 extension. The results of the normality test showed that the data was not normally distributed, so the correlation analysis was carried out using Spearman Rank. The results showed a significant positive relationship between the learning outcomes of the Basic Elements of Patterns and the learning outcomes of the Elements of Preparation for Fashion Preparation with a significance value (Sig 2 tailed) of 0.000 (p < 0.05) and a correlation coefficient of 0.618. These findings show that the mastery of basic competencies in phase E contributes to the achievement of advanced competencies in phase F. Thus, learning outcomes in each learning element in the Independent Curriculum are interrelated and sustainable, especially in learning Fashion at Vocational Schools.